2015
DOI: 10.1115/1.4030859
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of Laser Surface Texturing on Friction and Wear Behavior of Graphite Cast Iron

Abstract: Dimples with various pitches and densities were produced using laser surface texturing (LST) to improve the friction and wear behavior of graphite cast iron. The objective of this study is to investigate the effectiveness of dimples on the friction and wear behavior of an internal combustion engine (ICE) cylinder. The specimens with a dimple pitch of 150 μm and a dimple density of 13% exhibited the lowest friction coefficient among the specimens, while the specimens with a dimple pitch of 200 μm and a density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…12 also elucidates the wear mechanism associated with the contact surfaces. 16 The abrasive grooves that were visible on the specimens show that the wear was mainly abrasive.…”
Section: Wear Behaviormentioning
confidence: 97%
“…12 also elucidates the wear mechanism associated with the contact surfaces. 16 The abrasive grooves that were visible on the specimens show that the wear was mainly abrasive.…”
Section: Wear Behaviormentioning
confidence: 97%
“…Yin et al (2019) established a lubrication model considering surface roughness for textured cylinder liners and found that by fabricating surface texture the lubrication performance of cylinder liners was increased and wear was reduced. Tripathi et al (2016) performed a ball-on-disk tribological test to evaluate the tribological performance of the specimens. A certain operation condition was selected and laser surface texturing (LST) was used to fabricate surface texture.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies reveal that, these microtextures act like micropockets for wear debris in either dry or lubricated sliding conditions. These microstructures also act as microreservoirs for lubricant under the conditions of lubrication starvation and are predictable to form a lubricating film which leads to reduced friction 21–23 …”
Section: Introductionmentioning
confidence: 99%